Molecular Genetic Characteristics of Different Scenarios of Xylogenesis on the Example of Two Forms of Silver Birch Differing in the Ratio of Structural Elements in the Xylem - Natalia A. Galibina; Tatiana V. Tarelkina; Olga V. Chirva; Yulia L. Moshchenskaya; Kseniya M. Nikerova; Diana S. Ivanova; Ludmila I. Semenova; Aleksandra A. Serkova; Ludmila L. Novitskaya (Plants, 2021)
Silver birch (Betula pendula Roth) is an economically important species in Northern Europe. The current research focused on the molecular background of different xylogenesis scenarios in the birch trunks. The study objects were two forms of silver birch, silver birch trees, and Karelian birch trees; the latter form is characterized by the formation of two types of wood, non-figured (straight-grained) and figured, respectively, while it is currently not clear which factors cause this difference. We identified VND/NST/SND genes that regulate secondary cell wall biosynthesis in the birch genome and revealed differences in their expression in association with the formation of xylem with different ratios of structural elements. High expression levels of BpVND7 accompanied differentiation of the type of xylem which is characteristic of the species. At the same time, the appearance of figured wood was accompanied by the low expression levels of the VND genes and increased levels of expression of NST and SND genes. We identified BpARF5 as a crucial regulator of auxin-dependent vascular patterning and its direct target—BpHB8. A decrease in the BpARF5 level expression in differentiating xylem was a specific characteristic of both Karelian birch with figured and non-figured wood. Decreased BpARF5 level expression in non-figured trees accompanied by decreased BpHB8 and VND/NST/SND expression levels compared to figured Karelian birch trees. According to the results obtained, we suggested silver birch forms differing in wood anatomy as valuable objects in studying the regulation of xylogenesis.